2018
DOI: 10.11646/phytotaxa.365.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Staurosira and Pseudostaurosira (Bacillariophyta) from the highlands of Argentina (south-central Andes) and two new nomenclatural combinations

Abstract: Two new araphid diatom (Bacillariophyta) species, Pseudostaurosira oliveraiana sp. nov. and Staurosira catamarcensis sp. nov. are described from fossil material taken from the saline Laguna Colorada (Argentinian Altiplano). The morphology of the new species is studied using both light (LM) and scanning electron microscopy (SEM) and is compared to that of similar taxa. Pseudostaurosira oliveraiana sp. nov. is different from other species of Pseudostaurosira by its linear to lanceolate valve outline, with apices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
5
0
4
Order By: Relevance
“…Las especies pertenecientes a los géneros Staurosira y Pseudostaurosira poseen mayor número de registros en la bibliografía, si bien han sufrido múltiples revisiones desde su descripción original (Cejudo-Figueiras et al, 2011;Grana et al, 2018). Staurosira es un género antiguo redefinido luego de la revisión del género Fragilaria.…”
Section: Discusión Fragilarioides Fósiles Del Río Coloradounclassified
See 3 more Smart Citations
“…Las especies pertenecientes a los géneros Staurosira y Pseudostaurosira poseen mayor número de registros en la bibliografía, si bien han sufrido múltiples revisiones desde su descripción original (Cejudo-Figueiras et al, 2011;Grana et al, 2018). Staurosira es un género antiguo redefinido luego de la revisión del género Fragilaria.…”
Section: Discusión Fragilarioides Fósiles Del Río Coloradounclassified
“…La disposición marginal de las estrías genera un área axial amplia en la valva (Figura 3H). Posee campos de poros reducidos y por lo general las espinas interrumpen las estrías (Grana et al, 2018). Pseudostaurosira ha sido definido tradicionalmente como un género con representantes salobres-dulceacuícolas oligotróficos a mesotróficos [e.g.…”
Section: Discusión Fragilarioides Fósiles Del Río Coloradounclassified
See 2 more Smart Citations
“…Reliably species indicators include P. glubokoensis, P. oliveraiana and D. tenuis which in turn displayed the highest conductivity optima. Grana et al (2018) identified to P. oliveraiana in Holocene sediments from the saline Laguna Colorada (Argentinian Altiplano). Although other small araphid diatoms as S. venter, P. brevistriata and P. lancettula also show high inferred optima, they are poor indicators of conductivity because they present wide tolerances.…”
Section: Species Optimamentioning
confidence: 99%